Effect of polymer molecular weight and solution parameters on selective dispersion of single-walled carbon nanotubes - Jakubka, Florian; Schießl, Stefan; Martin, Sebastian; Englert, Jan; Hauke, Frank; Hirsch, Andreas; Zaumseil, Jana (ACS Macro Letters, 2012)
The selective dispersion of single-walled carbon nanotube species (n,m) with conjugated polymers such as poly(9,9-dioctylfluorene) (PFO) and poly(9,9-dioctylfluorene-cobenzothiadiazole) (F8BT) in organic solvents depends not only on the type of solvent but also on the molecular weight of the polymer. We find an increasing amount of nanotubes and altered selectivities for dispersions with higher molecular weight polymers. Including the effects of different aromatic solvents, we propose that solution viscosity is one of the factors influencing the apparent selectivity by changing the reaggregation rate of the single-walled carbon nanotubes (SWNT). The type of solvent, polymer molecular weight, concentration, and viscosity should thus be taken into account when screening for new polymers for selective SWNT dispersion. © 2012 American Chemical Society.